Osoba po przeszczepieniu narządu doświadczająca jakości życia – jako przedmiot zainteresowań pedagogów - Cymerman, Iwona (Kultura-Społeczeństwo-Edukacja, 2012)
Pedagogy has been recently becoming more and more interdisciplinary, deriving from achievements of others humanities. In modern, complicated world it could be rather impossible not to bene t from such advantage, as it would push aside pedagogy and others elds of knowledge to margin, falling it back rather than giving them prospect of growth. That is why issue of organ transplantation, for instance, although it seems stricte medical problem, now expands area of pedagogy interests. It concerns all the situations having signi cance in experiencing quality of life by the pedagogical entities, so pupils in each age. This text is based on description of experiencing life’s quality of one person, living thanks to liver transplantation. It had been 10 years after surgery when Zygmunt was giving me interview. I hold a second conversation with him, as earlier he had been exchanging with me his experiencing quality of life. For the rst time I met my interlocutor in September 2001, at that moment, he had been only three months after transplantation. Experiencing day–to day–reality of family, work, seeing with medical personnel during necessary consultation, this time were important for me. As a scientist I was interested also in changes that had been emerging and still appears in the context of quality life experiencing, from that moment when we had a rst conversation. Feeling of life sense, recognized values were signi cant for me. Quality analysis, having attributes of phenomenological description of experiencing Zygmunt’s quality life is often supplementing by medical, legal, ethical and religious data. I have done this, so that to in abbreviated way expose issues, shaping new research elds and new areas of educators’ activities in the context of transplantation. Zygmunt’s narrative is individual and for that reason it is not justi ed to make generalized conclusions. In the last part of text I am taking up e orts to justify signi cance of discussed issue (experiencing quality of life after transplantation).